Ablation of conceptus PTGS2 expression does not alter early conceptus development and establishment of pregnancy in the pig. Issue 2 (16th October 2019) - Pfeiffer, Caroline A; Meyer, Ashley E; Brooks, Kelsey E; Chen, Paula R; Milano-Foster, Jessica; Spate, Lee D; Benne, Joshua A; Cecil, Raissa F; Samuel, Melissa S; Ciernia, Lauren A; Spinka, Christine M; Smith, Michael F; et al.
Abstract: Pig conceptuses secrete estrogens (E2), interleukin 1 beta 2 (IL1B2), and prostaglandins (PGs) during the period of rapid trophoblast elongation and establishment of pregnancy. Previous studies established that IL1B2 is essential for rapid conceptus elongation, whereas E2 is not essential for conceptus elongation or early maintenance of the corpora lutea. The objective of the present study was to determine if conceptus expression of prostaglandin-endoperoxide synthase 2 (PTGS2) and release of PG are important for early development and establishment of pregnancy. To understand the role of PTGS2 in conceptus elongation and pregnancy establishment, a loss-of-function study was conducted by editing PTGS2 using CRISPR/Cas9 technology. Wild-type ( PTGS2 +/+ ) and null ( PTGS2 −/− ) fibroblast cells were used to create embryos through somatic cell nuclear transfer. Immunolocalization of PTGS2 and PG production was absent in cultured PTGS2 −/− blastocysts on day 7. PTGS2 +/+ and PTGS2 −/− blastocysts were transferred into surrogate gilts, and the reproductive tracts were collected on either days 14, 17, or 35 of pregnancy. After flushing the uterus on days 14 and 17, filamentous conceptuses were cultured for 3 h to determine PG production. Conceptus release of total PG, prostaglandin F2⍺ (PGF2α), and PGE in culture media was lower with PTGS2 −/− conceptuses compared to PTGS2 +/+ conceptuses. However, the total PG, PGF2α, and PGE content in the uterine flushings was not different. PTGS2 −/− conceptus surrogates allowed to continue pregnancy were maintained beyond 30 days of gestation. These results indicate that pig conceptus PTGS2 is not essential for early development and establishment of pregnancy in the pig. Abstract : Summary Sentence Ablation of pig conceptus PTGS2 expression decreases prostaglandin production but does not affect pregnancy establishment and maintenance to 35 days of gestation.